Eksplorasi Pengaruh Tingkat Kecemasan Guru Sekolah Dasar terhadap Sikap terhadap Integrasi Teknologi - Victoria Olubola Adeyele (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
The integration of technology in the classroom is crucial for fostering a digital society, yet its success heavily relies on teachers' readiness. Despite the availability of technological tools, their effective adoption varies, often influenced by teachers' attitudes and anxiety levels. This study explores the the Influence of Primary School Teachers' Anxiety Levels on Attitudes Toward Technology Integration. Using a survey research design, data were collected from 126 teachers in government-owned primary schools. Attitudes were measured using a self-developed 4 Likert-scale instrument, while anxiety levels were assessed by adopting a standardized anxiety inventory. Results indicate that while teachers generally have positive attitudes toward technology integration, there is a notable prevalence of high anxiety levels that do not directly correlate with these attitudes. These findings suggest that other underlying factors contribute to anxiety, which warrants further investigation. The study recommends that schools establish support systems focused on enhancing teachers' mental well-being and competency in using technology. Future research should delve into identifying the specific factors that heighten anxiety in the context of technology adoption in education.